Training drills in high performance badminton—effects of interval duration on internal and external loads - Edel, Antonia; Weis, Jan-Luka; Ferrauti, Alexander; Wiewelhove, Thimo (Frontiers in Physiology, 2023)
Purpose: The aim of the present study was to analyze the impact of interval duration on training loads and technical skill performance in high performance badminton drills. Methods: On three experimental days, 19 internationally ranked players (13 male: 22.7±3.8 years, 180±6 cm, 71.5±6.1 kg; 6 females: 20.4±2.5 years, 168±4 cm, 59.8±6.0 kg) completed one of three protocols (T10, T30 and T50) of a typical badminton specific drill, the so-called “Multifeeding” (the coach feeds shuttlecock without break in a random order) in a counterbalanced order. The protocols varied in interval duration (10s, 30s and 50s) but were matched for the rally-to-rest-ratio (1:1) and active playing time (600s). Cardiorespiratory responses (portable spirometry, chest belt), energy metabolism (levels of blood lactate, La), rate of perceived exertion (RPE), player´s kinematics (Local Positioning System), and technical skill performance (video analysis) were measured. Results: Average oxygen consumption (T10 45±6; T30 46±7; T50 44±6 ml·min-1·kg-1), Energy expenditure (886±209; 919±176; 870±206 kcal·h-1), heart rate (164±13; 165±11; 165±10 bpm) and RPE (16±2; 17±2; 17±2) did not differ between the protocols. Respiratory exchange ratio (RER) and La significantly increased depending on interval duration (RER: 0.90±0.05; 0.93±0.03; 0.96±0.04 and La: 3.6±2.0; 5.6±3.0; 7.3±2.3 mmol·l-1). Stroke frequency (SF; 0.58±0.05; 0.57±0.05; 0.55±0.06 strokes·s-1) was similar while distance covered, and average running velocity were significantly lower for T50 compared to T10 (76±17; 70±13; 65±11 m·min-1). Jump frequency in T30 was higher than in T10 (6.7±3.1; 8.8±3.8; 8.5±4.2 jumps·min-1). Differences in internal and external loads were not associated with changes in stroke precision (errors: 16±6; 19±4; 18±4 %; accuracy: 22±6; 24±8; 23±8 %). Conclusion: Anaerobic metabolic stimulus increases while running distance and velocity decrease, in case of longer interval durations. Even though there was no impact on stroke precision, extending the intervals beyond 30s might impair external training load. Consequently, interval duration should be defined carefully depending on the training goals.